Effectiveness and characteristics of interventions to improve work participation in adults with chronic physical conditions: a systematic review. Issue 7 (27th March 2022) - Verhoef, Joan A. C.; Bal, Marjolijn I.; Roelofs, Pepijn D. D. M.; Borghouts, Jeroen A. J.; Roebroeck, Marij E.; Miedema, Harald S.
Abstract: Purpose: Chronic physical conditions often negatively affect work participation. The objective of this systematic review is to investigate the effectiveness and characteristics of vocational rehabilitation interventions for people with a chronic physical condition. Methods: Searches in five databases up to April 2020 identified 30 studies meeting our inclusion criteria. Two reviewers independently assessed and extracted data. The Grading of Recommendation, Assessment, Development and Evaluation (GRADE) framework was used to evaluate quality of evidence for three outcome measures related to work participation. Results: All vocational rehabilitation interventions consisted of multiple components, but their characteristics varied widely. Analysis of 22 trials yielded a moderate positive effect with moderate certainty of interventions on work status; analysis of five trials with low risk of bias showed a large positive effect with moderate certainty (risk ratio 1.33 and 1.57, respectively). In addition, in eight studies we found a moderate to small positive effect with low certainty on work attitude (standardized mean difference = 0.59 or 0.38, respectively). We found no effect on work productivity in nine studies. Conclusion: The systematic review of the literature showed positive effects of vocational rehabilitation interventions on work status and on work attitude; we found no effect on work productivity. Implications for rehabilitation: In rehabilitation, addressing work participation of persons with a chronic physical condition using targeted interventions is beneficial to improve or sustain work participation, irrespective of the intervention characteristics and diagnosis. Interventions that include multiple components and offer individual support, whether or not combined with group sessions, are likely to be more effective in improving work participation in persons with a chronic physical condition. The overview of vocational interventions in this systematic review may assist healthcare professionals in making informed decisions as to which intervention to provide. Vocational rehabilitation, as well as studies on work participation in chronic disease, should include a long follow-up period to explore if work participation is sustainable and contributes to health and wellbeing.